PENDIDIKAN ADIL GENDER DI PONDOK PESANTREN (Studi tentang Membangun Gender Awareness di Pondok Pesantren Nurul Jadid Paiton Probolinggo) - Hambali Hambali (PEDAGOGIK : JURNAL PENDIDIKAN, 2017)
This research presents about building gender awareness in Nurul Jadid Paiton Probolingg through gender equitable education. Gender equitable education in Nurul Jadid Paiton Probolinggo is all educational activities that provide fair opportunity to all components of pesantren through gender awareness, both men and women to carry out their roles in educational activities to exercise their rights and obligations in accordance with their roles in a fair and wise. This research uses qualitative method with case study type. The results showed that; 1) Efforts made by the leadership of Pesantren Nurul Jadid Paiton Probolinggo in building gender awareness is done through; guidance on gender awareness or gender mainstreaming, change of mindset of pesantren civitas, equel gender relation, optimization of women participation in pesantren activity, development of gendered curriculum and reward and punishment. 2) Implication of the implementation of fair education in building gender awareness in Pondok Pesantren Nurul Jadid Paiton Probolinggo, that is; the quality of pesantren is increasing, the atmosphere of public relations and religious pesantren, the creation of harmonization in pesantren, decreased bias and gender gaps in education, optimizing the role of women in educational activities in pesantren.